AB1432-HPR Level of education, occupation and sleep disorders in patients with rheumatoid arthritis and relationship with disease activity. (23rd January 2014) - Villarreal, L.; Amador, L.; Bello, J.; Urbina, A.; Zambrano, D.; Santos-Moreno, P.
Abstract : Background: The rheumatoid arthritis (RA), as known, causes inability in various performance areas mostly in the musculoskeletal. Reduced physical activity, substantial disability and also sleep disorders have previously been described in people with RA. Objectives: The aim of this study was to describe the socio-demographic profile and sleep disorders in RA patients from a specialized RA clinic in Colombia. Methods: A descriptive cross-sectional study was performed in a specialized clinic dedicated to care patients with rheumatoid arthritis (RA). 127 patients were included in the study, which were seen by the area of psychology, which information was collected through semi-structured interviews and non-probability sampling. Descriptive epidemiology was applied for continuous variables, using measures of central tendency and dispersion for categorical and qualitative variables by averages and percentages. By means of Pearson's statistics it was analyzed bi-variated correlations. Results: The total sample of patients was 127, 103 (81.1%) were women and 24 (18.9%) were men, average DAS28-3.5±0.8. Average age is 53.4 years. 36% was married, 19.8% is divorced, 15.5% is single and others undefined. Related with the occupation, 31% is retired because age and the 17.9% have handicap retirement pay; 19.4% is dedicated to the housekeeping and 31.7% were working. Related to education 19.4% no education, 25% had elementary school, 29% didn't finish high school, 18.2 were technical and only 8.4% finish high school. Finally, 70 (55.2%) of patients report sleep disorders and 57 (44.8%) don't. It was found that 67 (95.7%) of reported patients linked sleep disorder with pain. Among type of sleep disorders were seen: primary insomnia (13.8% of women and 21.5% of men), nonspecific dyssomnias (6.7% of women and 7.9% of men), circadian rhythm disorder (5.1% of women and 13.2% of men), and hypersomnia in 0.93% of women. It was established a correlation between sleep disorders and disease activity (p<0.04), but not between level of education or occupation with disease activity. Conclusions: According to these findings sleep disorders are likely present in almost half of patients with RA and in many cases linked with pain. Primary insomnia and circadian rhythm disorder are more prevalent in men (probably because many of them work in night private guard). A higher DAS28 is expected to be associated with restless sleep, but level of education don't influence on disease activity. Disclosure of Interest: None Declared